Multiscale charge injection and transport properties in self-assembled monolayers of biphenyl thiols with varying torsion angles - Masillamani, Appan Merari; Thippeswamy, Ramakrishnappa; Zharnikov, Michael (Chemistry - a European journal, 2012)
This article describes the molecular structure-function relationship for a series of biphenylthiol derivatives with varying torsional degree of freedom in their molecular backbone when self-assembled on gold electrodes. These biphenylthiol molecules chemisorbed on Au exhibit different tilt angles with respect to the surface normal and different packing densities. The charge transport through the biphenylthiol self-assembled monolayers (SAMs) showed a characteristic decay trend with the effective monolayer thickness. Based on parallel pathways model the tunneling decay factor β was estimated to be 0.27 Å−1. The hole mobility of poly(3-hexylthiophene)-based thin-film transistors incorporating a biphenylthiol SAM coating the Au source and drain electrodes revealed a dependence on the injection barrier with the highest occupied molecular orbital (HOMO) level of the semiconductor. The possible role of the resistivity of the SAMs on transistor electrodes on the threshold voltage shift is discussed. The control over the chemical structure, electronic properties, and packing order of the SAMs provides a versatile platform to regulate the charge injection in organic electronic devices.
First published: 24 July 2012
Gesehen am 12.06.2018